Analisis Literasi Wisata Halal Destinasi Lombok Nusa Tenggara Barat - Dyah Pikanthi Diwanti; Sigit Ary Wijayanto (Jurnal Ilmiah Ekonomi Islam, 2023)
The World Superbike (WSBK) grand event completed at the Pertamina Mandalika International Street Circuit can be used as a momentum to revive halal tourism in Lombok, also known as the Thousand Mosques Island. The challenge that waits is the awareness of the people of Lombok, who still need to be encouraged by exploring their potential. This study aims to analyze the literacy level of halal tourism in Lombok. Data collection was further broken down into data collection, data reduction, data display, and conclusion/verification. The results show that literacy related to halal tourist destinations has not been fully understood by respondents (students) because there are still limited supporting things. However, the implementation of education and promotion efforts has been running, although it needs to be strengthened by other variables outside of this research, such as shifting interest from visual to digital promotion